(untitled) (Third Sector Social Economic Review, 2020)
In this study, Turkey’s 2009: 01-2019: 08 period with the amount of electricity from renewable energy sources wind produced from natural gas, hydropower, it is considered the relationship between the amount of electricity generated from geothermal and biofuels. Turkey natural gas and electricity from renewable sources produced by the correlation unit roots tests before the series to determine the VAR model was estimated and Johansen cointegration test. In addition, Error Correction Model, Variance Decomposition, Effect-Response analysis were also performed. The findings show that electricity production from hydroelectricity and biofuels and electricity from natural gas have a positive relationship and wind and geothermal energy production have a negative relationship. Findings of Turkey’s goal of pulling the gas utilization rate below 30% in electricity production and in the direction of achieving the environmental objectives of the Kyoto Protocol is expected to be data.